OP0061 Update of Eular Recommendations for the Treatment of Systemic Sclerosis. (9th June 2015) - Kowal-Bielecka, O.; Fransen, J.; Avouac, J.; Becker, M.; Kulak, A.; Allanore, Y.; Distler, O.; Czirjak, L.; Denton, C.P.; Fligelstone, K.; Welling, J.; Mueller-Ladner, U.
Abstract : Objectives: The aim was to update the 2009 EULAR recommendations for the treatment of systemic sclerosis (SSc) [1] with a distinct focus on new therapeutic aspects. Methods: Revision and update of the previous recommendations were performed according to the EULAR standard operating procedures. The task force consisted of 30 SSc experts from Europe and USA, two patients nominated by the pan-European patients association FESCA, a clinical epidemiologist and 3 fellows for systematic literature research. All centers from the EULAR Scleroderma Trials and Research (EUSTAR) group were invited to submit and select research questions concerning SSc treatment using a Delphi approach. A set of 46 research questions addressing 26 different interventions was selected for systematic literature research. The new recommendations were developed in a meeting, based on the available evidence while using a consensus procedure. Results: Sixteen recommendations were developed (instead of 14 in 2009) which address treatments of several SSc-related organ complications: Raynaud's phenomenon (RP), digital ulcers (DUs), pulmonary arterial hypertension (PAH), skin and lung disease, scleroderma renal crisis, and gastrointestinal involvement. Compared with the 2009 recommendations, the 2015 recommendations include phosphodiestase-5 (PDE5) inhibitors in the treatment of SSc-related RP and DUs, riociguat and new aspects for endothelin receptor antagonists, prostacyclin analogues and PDE5 inhibitors for SSc-related PAH. The new recommendations regarding the use of fluoxetine for SSc-related RP and haematopoietic stem cell transplantation for selected patients with rapidly progressing SSc were added. In addition, the statement regarding sitaxentan for PAH was removed, because it was withdrawn from the market. A web-based internal evaluation of the new recommendations revealed high level of approval among task force members (average score >7 out of maximum 9) for all statements except the one regarding fluoxetine for RP (average score of 6, 1). In addition, several comments regarding other treatments addressed in research questions and suggestions for the future SSc research agenda were formulated by the experts. Conclusions: These updated and improved, data- and consensus-derived recommendations will help rheumatologists to manage patients with SSc in an evidence-based way. These recommendations will also facilitate the directions for future clinical research in SSc. References: Kowal-Bielecka et al. Ann Rheum Dis 2009;68:620) Acknowledgements: The project is funded by a research grant of EULAR to the EUSTAR SSc recommendation group. All contributing experts will be listed as full coauthors on the respective presentations and publications. Disclosure of Interest: O. Kowal-Bielecka Speakers bureau: Abbvie, Actelion, Pfizer, Roche, J. Fransen: None declared, J. Avouac: None declared, M. Becker Consultant for: Actelion, A. Kulak: None declared, Y. Allanore Consultant for: Bayer Pharma, Actelion, Pfizer, Sanofi-Aventis, CSL Behring, Roche, O. Distler Consultant for: 4D Science, Actelion, Active Biotec, Bayer-Schering, Biogen, Biovitrium, BMS, Boehringer Ingelheim Pharma, EpiPharm, Ergonex, GSK, Inventiva, Medac, Novartis, Pfizer, Pharmacyclics, Roche/Genentech, Sanofi/Genzyme, Serodapharm, Sinoxa and United BioSource Corporation., L. Czirjak Consultant for: MSD, Pfizer, Roche, Abbvie, UCB, BMS, Servier, Medac, Richter, Egis, C. Denton Grant/research support from: Actelion, CSL Behring, Novartis, Consultant for: Actelion, GSK, Bayer, Inventiva, Takeda, K. Fligelstone: None declared, J. Welling: None declared, U. Mueller-Ladner Grant/research support from: EULAR grant